Effects of Harvest Time and Storage Form on Insect Population and Damage of Maize - Asare, Sharon G.; Kwarteng, S. A.; Owusu, B. S.; Baidoo, P. K. (Talenta Publisher, 2023)
The aim of this study was to determine the effects of harvest time and storage form on population levels of insect pests and their damage on stored maize. Maize was cultivated on a total land area of 19 x 23m2 during the major season (April to August 2020) and minor season (September to December 2020). Maize was harvested at three stages; early harvest, mid harvest and late harvest. Harvested maize was stored in three ways; husked, de-husked and shelled. Analysis of variance (ANOVA) was applied to the data through Sisvar version 5.6. Insect pests that were sampled during the study were Sitophilus zeamais, Cathartus quadricollis, Carpophilus dimidiatus and Tribolium castaneum. Carpophilus dimidiatus were sampled from treatments during the major season whereas Tribolium castaneum was sampled during the minor season. Sitophilus zeamais and Cathartus quadricollis were sampled in both seasons.Â In the major season, late harvest shelled maize (LHS) recorded 689% more S. zeamais numbers as compared to early harvest husked maize (EHH). Mid-harvest husked maize (MHH) had 307% less number of S. zeamais compared to LHS in the minor season. Late-harvest shelled maize (LHS) had the highest percentage insect damaged kernels (86.94%) in the major season.